Assessment of energy efficiency and performance in a two-phase anaerobic process for organic matter removal - Andrea D. P. Hurtado (IWA Publishing, 2021)
Energy efficiency (EE) depends mainly on the lower heating values (LHVs) of hydrogen and methane selected from the thermodynamics tables under ideal conditions. However, for practical applications, the heating value should be calculated by considering some environmental factors under real conditions. Accordingly, this study compared EE using the ideal LHV with the EE using the real LHV in a two-phase anaerobic digestion reactor treating synthetic wastewater. Additionally, the process performance and the stability were studied. The results showed that the EE value calculated using LHVideal was, on average, 35% higher than that evaluated using LHVreal; these differences are relevant to the estimation of real energy and also for practical applications. At the same time, the index buffer intermediate alkalinity/partial alkalinity was shown to be more accurate than the pH value to analyze the stability of the process. With regards to chemical oxygen demand, the removal efficiency in the methanogenic phase decreased drastically when utilizing 100% of the acidogenic phase. Future considerations for the optimization of each phase are highlighted. HIGHLIGHTS Lower heating value should be adjusted to estimate the energy efficiency.; Different approaches are considered to evaluate the energy gain and the energetic efficiency in a anaerobic digestion process in two phases.; The IA/PA ratio is recommended as a process indicator if compared only with the pH value.;